[Presbyterian Church in the U.S.A. Board of Foreign Missions correspondence and reports, 1833-1911 : Philippine] - Presbyterian Church in the U.S.A. Board of Foreign Missions ([Wilmington, Del.] : Scholarly Resources)
Includes incoming correspondence from the mission field, outgoing correspondence from the Board headquarters, diary accounts, sermon manuscripts, minutes of board meetings and annual reports on mission work.
Rolls 287-288 - Mexico/Philippines ; 280 ; 290 - Philippines/Siam.
Title supplied by cataloguer; set created from reels with non-consecutive numbering.
Philippine Mission 1898-1910.
Keywords: Presbyterian Church in the U.S. -- Missions -- Philippines -- History -- Sources; Missions -- Philippines -- History; Philippines -- Church history -- Sources